Efficacy of Pulsatilla saponin B4 for treatment dairy cows affected with clinical mastitis - Hao Zhang; Dan Shao; Zhen Yang; Shengyi Wang; Yue Zhang; Haoyu Peng; Zhetong Su; Yong Zhang (PLoS ONE, 2025)
In order to explore the therapeutic effect of natural compound Pulsatilla saponin B4 (PSB4) on clinical mastitis (CM) in dairy cows, 40 dairy cows with CM and 20 healthy dairy cows were selected as experimental samples in a large dairy farm. The CM cows were randomly divided into two groups (20 cows in each group), namely the PSB4 group treated with PSB4 neck intramuscular injection and the positive drug (PC) group treated with ceftiofur sodium neck intramuscular injection as a positive control. Another 20 healthy dairy cows were neck intramuscular injected with the same amount of normal saline to serve as a normal control (NC) group. The treatment duration was 7 days. The body temperature and milk yield of all cows were recorded on days 0, 4 and 7, while blood and milk samples were collected for the determination of relevant laboratory indicators, including somatic cell count (SCC), pathogenic microorganisms, immune factors, cytokines, antioxidant indexes, hematological and biochemical indexes. The results showed that PSB4 effectively restored the body temperature of diseased cattle, reduced SCC, significantly increased milk yield, effectively inhibited pathogenic bacteria, and significantly restored the levels of serum C-reactive protein (CRP), interleukin-1α (IL-1α), interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-8 (IL-8), tumor necrosis factor-α (TNF-α); immunoglobulin A (IgA), immunoglobulin G (IgG), immunoglobulin M (IgM); total antioxidant capacity (T-AOC), superoxide dismutase (SOD), malondialdehyde (MDA), glutathione peroxidase (GSH-Px) and other indicators. In addition, some indicators of blood routine and blood biochemistry also returned to normal levels. In summary, PSB4 has a significant therapeutic effect on CM in dairy cows, and has a similar effect to the positive drug, which can provide a new strategy for reducing the use of antibiotics in dairy cattle farms.